Eucalyptus-derived essential oils alleviate microbes and modulate inflammation by suppressing superoxide and elastase release - Fayez, Shaimaa; Gamal El-Din, Mariam I.; Moghannem, Saad A.; Azam, Faizul; El-Shazly, Mohamed; Korinek, Michal; Chen, Yu-Li; Hwang, Tsong-Long; Fahmy, Nouran M. (Frontiers in Pharmacology, 2023)
The Eucalyptus tree, belonging to the myrtle family, grows all over the world for its pharmaceutical and industrial benefits. In this article, we present a comparative analysis of the chemical composition of the hydrodistilled oils obtained from three different Eucalyptus species growing in Egypt viz. E. citriodora, E. camaldulensis, and E. ficifolia. Gas Chromatography-Mass Spectrometric guided analysis resulted in the identification of a total of 20 metabolites in E. citriodora oil with citronellal (54.9%) and citronellol (25.4%) being the most dominant components. β-cymene (12.7%) and 1,8-cineole (11.7%) were the major volatile constituents identified in E. camaldulensis oil, while trans-β-ocimene (22.4%), 1,8-cineole (13.5%), and L-trans-pinocarveol (12.5%) were the dominating components in the oil of E. ficifolia. The essential oils of the studied species were evaluated for their in vitro anti-inflammatory, antiviral including anti-SARS-CoV-2 (severe acute respiratory syndrome corona virus 2), antibacterial, and antifungal activities. E. citriodora oil displayed the highest inhibitory activity on the release of the superoxide radical (32%) and elastase enzyme (31%) in human neutrophils, while E. ficifolia oil had enhancing effects on elastase. The latter showed significant antiviral effects against hepatitis A, herpes simplex, and coxsackie viruses with IC50 values at 2.1, 2.5, and 5.6 μg/mL, respectively. Moderate antibacterial and antifungal activities were observed for Eucalyptus oils with Staphylococcus aureus being the most susceptible bacterial strain. E. ficifolia oil, similarly, displayed the best antibacterial activity with minimum inhibitory concentration (MIC) value at ca. 25 μg/mL (for S. aureus). On the contrary, E. camaldulensis oil was the most active against Candida albicans with an MIC value at 45 μg/mL. In silico studies were performed with a number of macromolecular drug targets for confirming the biological activities of the identified compounds and for interpreting their ADME (absorption-distribution-metabolism-elimination) parameters.